The Evolution of Purchasing Models in the Semiconductor Supply Chain: A Literature Review - Johnson, Laquanda Leaven; Ebakivie, Oghenetejiri; Johnson, Sean M. (International Journal of Supply Chain Management, 2025)
Semiconductors are crucial components of modern technology, with uses ranging from communications to national security. As demand for semiconductors rises, it is critical to understand procurement methods, which have a considerable impact on pricing and supply chain dynamics. The study provides an in-depth analysis of the literature on the evolution of purchasing models in the semiconductor industry, including historical and current viewpoints. It analyzes four key purchasing models: direct purchasing, distributor purchasing, value-added resellers (VAR), and online purchasing, each with unique strategic advantages and problems that impact buyer-supplier relationships, cost, and delivery consistency. This study contributes to the literature through providing a comprehensive review of the semiconductor supply chain while exploring available purchasing models and identifying factors that help shape purchasing decisions. The research delves into the historical development of various models, their current implementation, and potential future trends. Additionally, the research identifies existing gaps in the literature and suggests areas for future investigation to further enhance supply chain efficiency and effectiveness. The findings from this study will provide valuable insights for the semiconductor industry, offering strategies to optimize their supply chain, improve resilience, and adapt to emerging challenges.